2010
DOI: 10.1007/s00268-010-0692-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Laryngeal Nerve Monitoring During Esophagectomy and Mediastinal Lymph Node Dissection

Abstract: Intraoperative RLN identification and monitoring during single-lung ventilation surgery is technically feasible, easy, and reliable. The introduction of standardized RLN monitoring during this type of surgery may reduce the incidence of permanent RLN paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…Hence, complications and survival rates were compared between the dissection group and the control group. First, we knew that the major complications of RLN injury included hoarseness, anastomotic fistula and pulmonary complications from previous studies (17,21,22). The number of complications in the dissection group was greater than in the control group, and the differences were statistically significant ( Table 5).…”
Section: The Scoring Systemmentioning
confidence: 88%
See 2 more Smart Citations
“…Hence, complications and survival rates were compared between the dissection group and the control group. First, we knew that the major complications of RLN injury included hoarseness, anastomotic fistula and pulmonary complications from previous studies (17,21,22). The number of complications in the dissection group was greater than in the control group, and the differences were statistically significant ( Table 5).…”
Section: The Scoring Systemmentioning
confidence: 88%
“…Damage of RLNs includes resection, blood supply blockage for nerve nutrition, thermal damage, incorrect ligation, contusion and traction. The function of the vocal cords will recover in one year postoperatively, which depends on the extent of the laryngeal recurrent nerve injury (17). The diagnostic process for laryngeal recurrent nerve injury is based on a previous report (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative RLN monitoring is widely used in thyroid and parathyroid surgery. This technique, which is based on an electrically stimulated response, has recently been adopted for intrathoracic surgeries, and several investigators have demonstrated the technical feasibility and clinical benefits for reducing the incidence of RLNP and postoperative pneumonia among patients undergoing transthoracic esophagectomy (Gelpke et al 2010;Zhong et al 2014). Surgeons usually use electrocautery for hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RLNP after esophagectomy varies, ranging from 0% to 59% (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These disparities have been attributed to variation in extent of lymph node dissection, surgical technique (two-or three stage), the size and T-stage of the primary tumor, and the means of RLN injury diagnosis (8,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%